Residual fluxes of mass, salt, temperature and suspended sediment through a section of Bahia Blanca - Pérez, Daniel E. (1998)
Observations of currents, salinity, suspended load for a section of the Bahia Blanca estuary are presented and the residual fluxes of these variables are estimated. The variables were measured at two stations over a complete spring tidal cycle. Data are analyzed employing a proportional grid which provided the residual fluxes and the Euler and Lagrangean residual currents and Stokes drift. The cross-section is partly mixed but there is a significative amount of water entering the Principal Channel from the southern tidal flats during ebb.